Gastric Cancer and Helicobacter pylori: Impact of hopQII Gene - Kazemi, E; Kahrizi, D; Moradi, M T; Sohrabi, M; Yari, K (Cellular and Molecular Biology, 2016)
The Helicobacter pylori is a Gram-negative, microaerophilic bacterium found usually in the stomach and use a number of mechanisms to survive in the stomach lumen. The presence of these bacteria in the stomach can lead to gastritis and reduction in stomach acid production. Acute inflammation can directly damage to the peripheral cells that are responsible for the secretion of acid. The risk of developing gastric carcinoma is associated to heterogeneity of Helicobacter pylori virulence factors. The HopQII is one of the outer membrane proteins involved in bacterial adherence to gastric mucosa and has been suggested to also play a role in the virulence of H. pylori. The purpose of the current study was to investigate the association between different H. pylori virulence hopQII allele and patients with gastroduodenal disorders. For this purpose 58 stomach biopsies of patients with gastric cancer and 100 saliva samples from healthy individuals were collected. Then genomic DNA was purified and PCR for was done for desired genes via specific primers. The H. pylori infections were diagnosed by PCR for GlmM gene. Then frequencies of hopQII+ and hopQII- genotypes was determined in H. pylori infected cases. Statistical analysis showed that there were not significant differences between healthy and diseased ones for genotype hopQII+.